The Anthology of Babel - Simon, Ed (punctum books, 2020)
Why should there only be literary scholarship about authors who actually lived, and texts which exist? Where are the articles on Enoch Campion, Linus Withold, Redondo Panza, Darshan Singh, or Heidi B. Morton? That none of these are real authors should be no impediment to interpreting their invented writings. In the first collection of its kind, The Anthology of Babel publishes academic articles by scholars on authors, books, and movements that are completely invented. Blurring the lines between scholarship and creative writing, The Anthology of Babel inaugurates a completely new literary genre perfectly attuned to the era we live in, a project evocative of Jorge-Louis Borges, Umberto Eco, and Italo Calvino.